Edoxaban for the Long‐Term Therapy of Venous Thromboembolism: Should the Criteria for Dose Reduction be Revised? - Giuseppe Camporese; Paolo Simioni; Pierpaolo Di Micco; Carmen Fernández‐Capitán; Agustina Rivas; Carme Font; Joan Carles Sahuquillo; Paula Villares; Paolo Prandoni; Manuel Monreal; and the RIETE Investigators (Wiley, 2021)
Edoxaban is used for venous thromboembolism (VTE) treatment. Real‐life data are lacking about its use in long‐term therapy. We aimed to assess the efficacy and the safety of edoxaban for long‐term VTE treatment in a real‐life setting. Patients with VTE included in the Registro Informatizado Enfermedad TromboEmbólica (RIETE) registry, receiving edoxaban 60 or 30 mg daily were prospectively followed up to validate the benefit of using different dosages. The main outcome was the composite of VTE recurrences or major bleeding in patients with or without criteria for dose reduction. Multivariable analysis to identify predictors for the composite outcome was performed. From October 2015 to November 2019, 562 patients received edoxaban for long‐term therapy. Most (94%) of the 416 patients not meeting criteria for dose reduction received 60 mg daily, and 92 patients meeting criteria (63%) received 30 mg daily. During treatment, two patients developed recurrent VTE, six had major bleeding and nine died (2 from fatal bleeding). Among patients not meeting criteria for dose reduction, those receiving 30 mg daily had a higher rate of the composite event (hazard ratio (HR) 8.37; 95% confidence interval (CI) 1.12-42.4) and a significant higher mortality rate (HR 31.1; 95% CI 4.63-262) than those receiving 60 mg. Among patients meeting criteria for dose reduction, those receiving 60 mg daily had no events, and a nonsignificantly higher mortality rate (HR 5.04; 95% CI 0.54-133) than those receiving 30 mg daily. In conclusion, edoxaban seems to be effective and safe for long‐term VTE treatment in real life. Criteria for dose reduction should be reformulated.